2022
DOI: 10.1155/2022/4209020
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Recognition Method of Video Basketball Technical Action Based on Target Detection Algorithm

Abstract: Aiming at the problems of poor real-time recognition efficiency and low recognition accuracy of video basketball technical movements, a real-time recognition method of video basketball technical movements based on the target detection algorithm is proposed. This study firstly collects video basketball technical action images and detects their edge contour features. Through machine vision block template matching processing, the video basketball technology motion capture results are output. Then, according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…Real-time correction, especially in the initiation stage of basketball, through informational technologies and observational methods, constitutes the premises for improving execution technique and performance efficiency, thereby optimizing basketball performance (Du et al, 2024;Zhu, 2022). Based on the aforementioned arguments and literature review, we consider our study relevant due to the theoretical and practical implications identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-time correction, especially in the initiation stage of basketball, through informational technologies and observational methods, constitutes the premises for improving execution technique and performance efficiency, thereby optimizing basketball performance (Du et al, 2024;Zhu, 2022). Based on the aforementioned arguments and literature review, we consider our study relevant due to the theoretical and practical implications identified.…”
Section: Introductionmentioning
confidence: 99%
“…Corectat în timp real, în special în etapa de inițiere în jocul de baschet, prin intermediul tehnologiilor informationale si prin metodele observationale constituie premisele îmbunătățirii tehnicii de execuție și a eficacității acestora determined optimizarea performanței sportive în baschet (Du et al, 2024;Zhu, 2022). Pe baza argumentelor mentionate anterior si pe baza studierii literaturii de specialitate, consideram ca studiul nostru este de actualitate prin implicatiile teoretice si practice identificate.…”
Section: Introducereunclassified